PENGEMBANGAN ARMADA PANCING TUNA DENGAN RUMPON DI PERAIRAN PUGER, JAWA TIMUR (The Development of Troll Lines Using Fish Agregation Device (FADs) in Puger Waters, East Java) - Ratih Purnama Sari; Tri Wiji Nurani; Sugeng Hari Wisudo; . Zulkarnain (Bogor Agricultural University, 2014)
ABSTRACTFisheries sector is undergoing a crisis in global dimensions for the last few years caused of unsustainable consumption, overfishing, as well as the increasing of pollution and climate change distribution. One of the overfishing area is South coast Java Seas) where this has the potential resources of tuna included Puger waters. Tunas are catched by troll lines around fish aggregating devices (FADs). Increasing population of FADs can effect tuna resources such as: the size and qualities decreased. The results showed that the length of catched tunas were between 40-49 cm, the weights were from 0 to 3.5 kg, and the organoleptics were dominated on 6 scale. These indicated that tunas had the unexpected sizes and exportless. The rising of FADs utilization also contributed to the increasing insidence of conflicts among fishery stakeholders. There were three kinds of conlicts in Puger, such as: latent conflict (shipping crew and TPI), felt conflict (internal shipping crew), and manifest conflict (shipping crew-institution). Development strategy formula was conducted by SWOT analysis. The important thing for government to overcome these problems were continuing in area socializing, utilization programme of coastal area for integrated and sustainable fisheries.Key words: catch composition analysis, FADs, social conflict, strategy of fisheries development——-ABSTRAKSektor perikanan sedang mengalami krisis dalam dimensi global pada beberapa tahun terakhir ini. Hal ini disebabkan karena pola konsumsi yang tidak berkesinambungan, overfishing, dan polusi serta perubahan iklim. Salah satu wilayah yang mengalami overfishing adalah Samudera Hindia Selatan Jawa dimana wilayah ini memiliki sumberdaya tuna yang potensial. Wilayah tersebut mencakup Perairan Puger, Jawa Timur. Tuna ditangkap menggunakan alat tangkap pancing dan alat bantu rumpon. Peningkatan rumpon dapat mengakibatkan sumberdaya tuna menurun yang dilihat berdasarkan komposisi ukuran dan menimbulkan konflik diantara stakeholder. Sebagai tambahan, penangkapan tuna oleh armada pancing menunjukkan kualitas tuna yang rendah akibat penanganan yang buruk. Hasil penelitian menunjukkan bahwa komposisi ukuran tuna berada pada selang 40-49 cm dengan berat ikan pada selang 0-3,5 kg. Hal ini mengindikasikan bahwa tuna memiliki ukuran tidak layak tangkap dan ekspor. Terdapat tiga jenis konflik di Puger, seperti: Latent conflict (Nelayan rumpon dan TPI), felt conflict (antara nelayan rumpon), manifest conflict (nelayan rumpon dan instansi pemerintah). Perumusan strategi pengembangan dilakukan menggunakan analisis SWOT. Hal yang paling penting bagi pemerintah dalam mengatasi permasalahan tersebut adalah dengan adanya sosialisasi daerah, program pengembangan wilayah pesisir terpadu dan berkesinambungan.Kata kunci: analisis komposisi hasil tangkapan, rumpon, konflik sosial, strategi pengembanganperikanan